2a-1=(a+1)+7a+5

Simple and best practice solution for 2a-1=(a+1)+7a+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a-1=(a+1)+7a+5 equation:



2a-1=(a+1)+7a+5
We move all terms to the left:
2a-1-((a+1)+7a+5)=0
We calculate terms in parentheses: -((a+1)+7a+5), so:
(a+1)+7a+5
We add all the numbers together, and all the variables
7a+(a+1)+5
We get rid of parentheses
7a+a+1+5
We add all the numbers together, and all the variables
8a+6
Back to the equation:
-(8a+6)
We get rid of parentheses
2a-8a-6-1=0
We add all the numbers together, and all the variables
-6a-7=0
We move all terms containing a to the left, all other terms to the right
-6a=7
a=7/-6
a=-1+1/6

See similar equations:

| C(n)=10+1.5n | | -4=-k | | 12÷11/2=x | | 6x+14=100 | | 0.5=p | | 7=y-52 | | 7=c | | (t+5)210=41790 | | 10=y3+6 | | -5z^2-10z+24=0 | | (x^2)+x+8=3x+21 | | K=15t^2+64t+360 | | -1.5=-r | | (0.04+x)/x=1.22 | | -k=-2 | | 0=-4.9t^2+27t+10 | | E(4)=30h | | 5x3-8=12-8 | | ((-9+a)/15)=1 | | -26=-6u+4(u-5) | | 6u-20=8(u-2) | | 3^(4x+6)=81 | | (4x+3)=43 | | -20=d/5 | | 7x3=14 | | 2x+2(3×+4)=112 | | 2x+2(3x4)=112 | | 125=m | | 7v+8=5(v-2) | | -8(u+5)=-2u+8 | | 4(2x+1)=160 | | 2/x-1=3 |

Equations solver categories